Forest Management and Biomass Production for Energy: A Case Study in Calabria Region (Italy). (10th June 2016) - Marziliano, Pasquale A.; Lombardi, Fabio; Altieri, Valeria; Coletta, Vittoria; Menguzzato, Giuliano; Stillitano, Teodora; Marcianò, Claudio
Abstract: Among all renewable energy sources, forest biomass represents both an important alternative source to fossil fuels and an opportunity for the socio-economic development of various marginal mountain areas in Calabria. The aimof this study is to estimate the potential revenue from timber harvest in a mountainous area belonging to the Reggio Calabria District, which is showing a great interest in forest biomass production. Following a cost-benefit analysis and by considering all marketable wood assortments, the here applied assessment method allowed us to estimate the timber production of the study area, estimating the potential biomass amount production for energetic purposes. The investigated forest stands coveran area of about 12000 hectares, an appropriate spatial scale for biomass production. Results showed a significant productive capacity, estimated at about 174000 Euro year -1 for each type of timber product, even if the more consistent amounts derive from round wood assortments. The estimation of woody biomass available for energetic purposes, mainly deriving from residual wood and timber assortments was estimated on about 24200 tons year -1 . The results obtained suggested how it could be possible, in the context of the Metropolitan city of Reggio Calabria, the creation of a small biomass energetic power station, with a generating capacity of about 1 MW.